PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH TERHADAP PROFESIONALISME GURU MATA PELAJARAN EKONOMI SMA NEGERI DI KABUPATEN KAMPAR - Filma Alia Sari; Yogi Riyantama Isjoni (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2021)
This study aims to see the magnitude of the influence of principal academic supervision on the professionalism of teachers in economics. This research is limited to the state high school unit group only, because there are so many private high schools in Kampar Regency. The method used is a survey method with correlational techniques. The population in this study were all 55 teachers of the economy at SMA Negeri Kampar Regency. The data in this study were collected by distributing questionnaires and documentation obtained from the principal. The data analysis technique used is descriptive analysis technique and inferential analysis. As well as using the data requirements test, namely: normality test and linearity test. The results showed that the magnitude of the influence of the principal's academic supervision on the professionalism of teachers in economics was 16.80%, while the remaining 83.20% was determined by other factors that were not part of this study.